Developmental programming: postnatal estradiol modulation of prenatally organized reproductive neuroendocrine function in sheep. Issue 2 (August 2016) - Puttabyatappa, Muraly; Cardoso, Rodolfo C; Herkimer, Carol; Veiga-Lopez, Almudena; Padmanabhan, Vasantha
Abstract : Gestational testosterone (TS) excess, acting via both the androgenic and estrogenic pathways, advances puberty and disrupts the neuroendocrine estradiol (E2 ) feedback and periovulatory hormonal dynamics in female sheep. These prenatally programmed defects may be subject to postnatal modifications by continued organizational and/or activational effects of steroids. This study investigated (1) the organizational contribution of prenatal estrogen excess and (2) the impact of postnatal exposure to E2 in modulating the effects of prenatal androgen excess (TS and dihydrotestosterone (DHT)) on puberty, neuroendocrine feedback mechanisms, and periovulatory hormonal dynamics in sheep. Pregnant Suffolk sheep were treated with TS, DHT, E2, or E2 plus DHT (ED) from days 30 to 90 of gestation. A subset of the control (C), TS, and DHT female offspring received a constant-release E2 implant postnatally. Findings revealed that (1) prenatal E2 -treatment failed to reproduce the neuroendocrine disruptions predicted to be programmed by the estrogenic pathway and (2) prenatal E2 D-treatment did not adequately replicate the reproductive neuroendocrine defects induced by prenatal TS excess. More importantly, continuous postnatal E2 -treatment, while delaying the onset of puberty and reducing the inhibitory effects of E2 on tonic luteinizing hormone (LH) release, failed to amplify the E2 -positive feedback and periovulatory defects induced by prenatal TS-treatment. Our results indicate that disruptions in E2 -positive feedback mechanisms and periovulatory gonadotropin secretion induced by prenatal TS-treatment are programmed predominantly during the prenatal life with postnatal exposure to E2 excess not contributing further to these disruptions.